THE GRAMMATICAL ERRORS IN GOOGLE TRANSLATION FROM INDONESIAN INTO ENGLISH OF ONLINE“SUMATERA EXPRESS” NEWSPAPER - Rahmawati Rahmawati (ELTE Journal (English Languange Teaching and Education), 2020)
The objective of this study was to describe the errors made in the Indonesian to English google translations of online Sumatera Express newspaper. This study employed five texts taken from online Sumatera Express newspaper made by using Google Translate. Five texts of the online Sumatera Express newspaper were analyzed. The categorization of translation errors was adapted from King and Stanley (1996), building Skills for Toefl. The errors can occur in the words, phrases, clauses, and sentences of the texts. The data gathered were analyzed descriptively by using a qualitative approach.The technique used was triangulation. The findings suggest that there were 12 grammatical errors included subject-verb agreement (3 errors), verbtense agreement (2 errors), word forms (1 error), reduced clause (1 error), connectors (3 errors), redundancy (1 error), and parallel structure (1 error). The conclusion suggested that there were 12 grammatical errors found in the five translated texts of online Sumatera Express newspaper, Google translation strategies used word by word translation without considering the actual meaning of the sentences and grammatical rules, English uses “Menerangkan-Diterangkan (M-D)” or “ModifierHeadword”, whereas Bahasa Indonesia uses “Diterangkan – Menerangkan (D-M) or ”Headword-Modifier”. And the theoretical implication for language teaching has explained in chapter four.